The dispersion measure in broadband data from radio pulsars - Rammala, Isabella (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2019)
Modern day radio telescopes make use of wideband receivers to take advantage of the broadband nature of the radio pulsar emission. We ask how does the use of such broadband pulsar data affect the measured pulsar dispersion measure (DM). Previous works have shown that, although the exact pulsar radio emission processes are not well understood, observations reveal evidence of possible frequency dependence on the emission altitudes in the pulsar magnetosphere, a phenomenon known as the radius-to-frequency mapping (RFM). This frequency dependence due to RFM can be embedded in the dispersive delay of the pulse profiles, normally interpreted as an interstellar effect (DM). Thus we interpret this intrinsic effect as an additional component Î´DM to the interstellar DM, and investigate how it can be statistically attributed to intrinsic profile evolution, as well as profile scattering. We make use of Monte-Carlo simulations of beam models to simulate realistic pulsar beams of various geometry, from which we generate intrinsic profiles at various frequency bands. The results show that the excess DM due to intrinsic profile evolution is more pronounced at high frequencies, whereas scattering dominates the excess DM at low frequency. The implications of these results are presented with relation to broadband pulsar timing.
Keywords: Pulsars; Radio astrophysics; Astrophsyics; Broadband communication systems